The Pivotal Role of Major Chromosomes of Sub-Genomes A and D in Fiber Quality Traits of Cotton - Razzaq, Abdul; Zafar, Muhammad Mubashar; Ali, Arfan; Hafeez, Abdul; Sharif, Faiza; Guan, Xueing; Deng, Xiaoying; Pengtao, Li; Shi, Yuzhen; Haroon, Muhammad; Gong, Wankui; Ren, Maozhi; et al. (Frontiers in Genetics, 2022)
Gossypium hirsutum L. is the most important tetraploid species cultivated over 33 million acres worldwide. The precise information about candidate genes involved in complex quantitative traits is a great hindrance to fiber quality improvement. As a result, the overall genetic gain is low in traditional phenotypic selection. Recent molecular interventions and advancements in genome sequencing have led to the development of high-throughput molecular markers, quantitative trait loci (QTL) fine mapping, and single nucleotide polymorphisms (SNPs) with genetic identification have resolved the existing bottlenecks in trait-specific breeding. This review demonstrates the significance of chromosomes 3, 7, 9, 11, and 12 of sub-genomes A and D carrying candidate genes for fiber quality. However, chromosome 7 carrying SNPs for stable and potent QTLs related to fiber quality provides great insights for fiber quality targeted research. This information can be validated by marker-assisted selection (MAS) and transgene in Arabidopsis and subsequently in cotton.